Readability Analysis and Accessibility of Online Materials About Transgender Voice Care. (December 2022) - Magrath, Walker J.; Shneyderman, Matthew; Bauer, Tom K.; Neira, Paula; Best, Simon; Akst, Lee M.
Objective: To determine readability, understandability, and actionability of online health information related to transgender voice care. Study Design: Review of online materials. Setting: Academic medical center. Methods: A Google search of "transgender voice care" was performed with the first 50 websites meeting inclusion criteria included. Readability was assessed using the Flesch Reading Ease Score (FRES), Flesch-Kincaid Grade Level (FKGL), and the Simple Measure of Gobbledygook (SMOG). Understandability and actionability were measured by 2 independent reviewers using the Patient Education Materials Assessment Tool for Printable Materials (PEMAT-P). Unpaired t tests were used to compare clinician- and patient-oriented sites, surgical and nonsurgical sites, and sites that discuss nonbinary indications for voice care. Analysis of variance was used to compare sites that discuss voice feminization, masculinization, both, or neither. Results: Average scores across the cohort for FRES, FKGL, and SMOG were 43.77 ± 13.52, 12.14 ± 2.66, and 11.30 ± 1.93, respectively, indicating materials were above a 12th-grade reading level. PEMAT-P scores for understandability and actionability were 64.95% ± 15.78% and 40.55% ± 23.86%, respectively. Patient-oriented sites were significantly more understandable and actionable than clinician-oriented sites ( P < .02). Websites that discussed only voice feminization were significantly more readable according to objective metrics (FKGL, SMOG) than websites that discussed both feminization and masculinization or those that did not differentiate care types ( P < .05). Conclusion: Online information written about transgender voice care is written at a level above what is recommended for patient education materials. Providers may improve accessibility of transgender voice care by enhancing readability of online materials.